Playing position as a predictor of strength and endurance among U-19 soccer players - Žuvela, F.; Cikotic, L.; Jelaska, I. (Acta Kinesiologica, 2025)
Purpose: The main goal of this research was to determine differences in strength and endurance between attack, midfield, and defense lines in young soccer players.